2016
DOI: 10.3892/mmr.2016.6073
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of PD-L1 by the human papillomavirus 16 E7 oncoprotein inhibits anticancer immunity

Abstract: Abstract. Cytotoxic T lymphocyte dysfunction is frequently associated with PD-L1/PD-1 pathway activation, and is a principal obstacle in cancer therapy. In the present study, the mechanisms underlying the human papillomavirus (HPV)-induced evasion of cervical cancer cells to the host immune system via the programmed death ligand 1/programmed death 1 (PD-L1/PD-1) signaling pathway was investigated. A significant increase in the expression of the HPV16E7 viral protein and PD-L1 in cervical tissues was observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Hypermethylation of Rad51B was shown in all three cancers to correlate with increased expression of both CTLA-4 and PD-L1 and hypermethylation of XRCC3 (also involved in homologous recombination) correlated with increased CTLA-4 expression in all three cancers [87]. The HPV E7 protein itself has also been shown to drive PD-L1 expression [88]. In addition, recent evidence has shown that E6 and E7 can lead to hypermethylation and silencing of various immune genes, such as type 1 interferons, HLA-E and CXCL14 [89].…”
Section: Pre-clinical Evidence Of Differences Between Human Papillomamentioning
confidence: 86%
“…Hypermethylation of Rad51B was shown in all three cancers to correlate with increased expression of both CTLA-4 and PD-L1 and hypermethylation of XRCC3 (also involved in homologous recombination) correlated with increased CTLA-4 expression in all three cancers [87]. The HPV E7 protein itself has also been shown to drive PD-L1 expression [88]. In addition, recent evidence has shown that E6 and E7 can lead to hypermethylation and silencing of various immune genes, such as type 1 interferons, HLA-E and CXCL14 [89].…”
Section: Pre-clinical Evidence Of Differences Between Human Papillomamentioning
confidence: 86%
“…In HPV-associated oropharyngeal squamous cell carcinoma, antigen-specific CD8 + T-cell infiltration into tumor is highly correlative with positive patient outcomes [33]. CD8 + T-cell functions are limited by either E7-mediated expression of suppressors such as PD-L1 or by low levels of antigen presentation [34,35]. To overcome this T-cell tolerance, several immunotherapies have been tested and approved by the FDA [36].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 – 4 ] Cervical cancer as a tumor had the most closely relation to HPV infection, the previous studies revealed that PD-L1 was a solid biomarker of productive HPV infection in the cervix, [ 5 ] and the overexpress of HPV16 E7 oncoprotein in the cervical epithelial carcinoma increased the expression level of the PD-L1 protein. [ 6 ] But all the reports first ignored the difference of PD-L1 between only HPV infection but cervical normal patients and HPV infection with cervical lesion patients; meanwhile, the samples of these studies were tissue specimens, neglecting the important of cervical exfoliated cells sample in cervical cell lesion study. At last, the previous studies did not include the relation between the specific HPV infection status and PD-L1 expression.…”
Section: Introductionmentioning
confidence: 99%